Ufd2p promotes efficient crossover formation by destabilizing Top2p during meiosis - Taicong Tan; Yanan Zhao; Yinghong Chen; Yali Mi; Jiaxin Zeng; Peng Du; Tingting Han; Yawen Liu; Ning Li; Jun Kong; Liying Wang; Yang Yu; et al. (Proceedings of the National Academy of Sciences, 2026)
Proper crossover (CO) formation in meiosis serves dual roles in ensuring accurate chromosome segregation and generating genetic diversity. However, the molecular mechanisms underlying CO number and distribution remain incompletely understood. Previous studies have implicated the ubiquitin–proteasome system in CO regulation, but specific regulators and mechanisms are poorly defined. Here, we identify the E3 ubiquitin ligase Ufd2p as a key regulator promoting efficient CO formation through a focused genetic screen in Saccharomyces cerevisiae . Deletion of UFD2 significantly reduces CO frequency by enhancing the strength of CO interference. Integrated multiomics analysis indicates that Ufd2p targets Topoisomerase II (Top2p) for ubiquitination and subsequent proteasomal degradation during meiosis. Deletion of UFD2 results in Top2p accumulation, which resolves DNA negative supercoils excessively and enhances CO interference in the nucleus, ultimately reducing CO numbers. We further show that the mammalian homolog of Ufd2p, UBE4B, plays a conserved role in promoting efficient CO formation by regulating TOP2A-dependent DNA negative supercoils dynamics. Notably, expression of mouse or human UBE4B in yeast restores CO formation and meiotic progression in UFD2 deletion cells, demonstrating functional conservation across species. Together, our work identifies Ufd2p as a previously uncharacterized regulator of CO formation and provides important insights into the conserved molecular mechanism, which operates through Top2p-mediated supercoils homeostasis.